Phubbing phenomenon: a digital dilemma in Gen-Z’s social life / Nurliyana Kamilah Khairul Anuar ...[et al.]. - Khairul Anuar, Nurliyana Kamilah; Ab Rashid, Faridah Hanem; Amanah, Farah Hazween; Ramlan, Muhammad Azril Izuan; Hassan @ Asan, Amirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The fast-paced technological advancement has indeed altered the standard societal life which has contributed to a newly discovered behaviour among younger generations, specifically the Gen-Z known as ‘phubbing’. The proliferation of portable technological devices such as smartphones and tablets is an integral part of Gen-Z’s life as through the times, these inventions are becoming as vital as the heartbeat that can no longer be separated. The extensive utilisation of social media applications and the fear of missing out (FOMO) among friends has influenced the phubbing behaviour among Gen-Z. This concerning behaviour has taken a toll on Gen-Z’s social life.